John Henry vs. the mighty steam drill - Meister, Cari.; Rivas, Victor (North Mankato, Minn. : Picture Window Books, a Capstone imprint, 2015)
Retells the legend of John Henry, an African-American hero who raced against a steam drill to lay railroad tracks on a mountain.
School Library Journal, November 2014
Includes bibliographical references (p. 31).
3.8
K-3
Keywords: John Henry (Legendary character) -- Legends; Folklore -- United States; Tall tales; John Henry (Legendary character) -- Legends; Folklore; Tall tales; John Henry (Legendary character) -- Legends; Folklore -- United States; Tall tales; Folklore; Tall tales; Legends